Common bacterial blight of common bean: insights into host resistance and bacterial virulence mechanisms - Alves, Francisco Henrique Nunes da Silva (2023)
Common Bacterial Blight (CBB), induced by the Gram-negative bacteria Xanthomonas phaseoli pv. phaseoli (Xpp) and Xanthomonas citri pv. fuscans (Xcf) is a substantial menace to common bean production worldwide. To contribute to unveiling the molecular mechanisms of host resistance and bacterial virulence subjacent to the interaction between common bean with Xanthomonas, in this study, first (Chapter 1) 80 common bean cultivars of the carioca and black groups were classified based on their resistance upon inoculation with a Xpp strain. The disease was assessed based on symptom severity and the Area Under Disease Progress Curve (AUDPC). The cultivars were subsequently grouped into four resistance/susceptibility categories according to their disease severity values. Three carioca and three black bean cultivars exhibited the lowest disease severity and AUDPC values and were classified as highly resistant to Xpp. A positive correlation between AUDPC and disease severity was observed. Following this classification, an exploratory Genome-Wide Association Study (GWAS) was undertaken using 384 Single Nucleotide Polymorphism (SNP) markers and data on disease severity from the same set of 80 cultivars. Five SNPs significantly associated with resistance were found on three different common bean chromosomes. These SNPs are within genes coding for a range of potential biochemical functions, including a light-regulated Lir1 protein, a proton-dependent oligopeptide transporter family protein, a metallo-dependent phosphatase-like protein, a WPP domain-interacting tail-anchored protein 2, and a pectin lyase-like superfamily protein. In the second phase (Chapter 2), aiming to explore the bacterial virulence mechanisms, 35 genome sequences of Xcf and 36 genome sequences of Xpp were utilized in pangenomic analyses and dendrogram constructions using gene presence/absence. The pangenomic analyses revealed significant genomic diversity and plasticity for both pathovars. The dendrograms did not indicate an evident clustering by geographic origin. Additionally, Xcf and Xpp genes activated by HrpG and HrpX were predicted bioinformatically searching for hrp box sequences within the promoter regions in their genomes. A total of 51 HrpG- and HrpX-dependent genes were found in Xcf and 49 genes in Xpp. Furthermore, to identify Type III Secreted Effectors (T3SEs), Blastp searches of all annotated proteins from the Xpp and Xcf genomes were conducted against databases of known Xanthomonas and Pseudomonas T3SEs. These searches led to the identification of 39 T3SEs, with the effector XopAL2 found exclusively in Xcf, six effectors were unique to Xpp, and seven effectors were shared with phytopathogenic Pseudomonas. This study brings significant contributions to the scientific community. It offers insights into common bean genotypes displaying high levels of resistance to Xpp, identifies candidate genes potentially associated with common bean resistance to Xpp, and sheds light on the mechanisms that Xanthomonas species might employ to cause disease in common bean plants. Keywords: Xanthomonas citri pv. fuscans. Xanthomonas phaseoli pv. phaseoli. Phaseolus vulgaris